Charts based on millions of fluid dynamics simulations provide a simple tool to estimate how far from its source a specific blood stain can be found. (May 2019) - Attinger, Daniel
Highlights: A large dataset of more than five million of numerically calculated trajectories of blood drops is produced and mined to determine the maximum distance between a blood stain and the source of the blood. The numerical results are presented as a set of charts that can be directly useful for investigative work in bloodstain pattern analysis. Results are presented using variables that are directly and easily observed on the crime scene, such as the stain size and its ellipticity. The packaging of complex physics into a tool that is simple to use and that does not require any knowledge of fluid dynamics is analog to a pregnancy test. Comparisons with existing reports of experiments and a limited set of experiments are consistent with the results of the proposed theoretical model. Abstract: The bloodstain pattern analyst sometimes has to judge if a given stain could originate from a specific location. A wide range of values of the maximum distance that a blood drop can travel have been reported from experiments, ranging from less than one meter to more than 10 m. Here we formulate the problem in a fluid dynamics and data mining framework. The fluid dynamics is solved with Newton's classical equation of motion coupled with well-established models for the gravity and drag forces that bend the trajectories of drops. The parameters screened are the drop size, initial velocity and launch angle, as well as the height of a blood source and the ceiling height. Combining a wide range of values of those five parameters commended the performance of more than 5 million fluid dynamic simulations. Results of these simulations have been searched and mined for parameters directly measurable on a crime scene, such as the stain size and stain ellipticity. The results are presented in simple, easy to use charts, which do not require any knowledge of fluid dynamics from the analyst.